Electrical Transport Properties of Ce2(WO4)3, Dy2(WO4)3 and Ho2(WO4)3 - Maurya, K.C.; Thakur, A.N.; Yadav, S.K. (Asian Journal of Chemistry, 2011)
The tungstate compounds of the type R2(WO4)3 (where R = Ce, Dy and Ho) have been prepared by a solid state reaction technique and characterized by XRD, DTA, TG and DTG. The XRD characterization suggests the formation fo single phase orthorhombic structure at room temperature. The electrical conductivity (σ) measurements on the pressed pellets have been reported in the temperature range 303 to 1103 K. It has been found that these compounds are essentially electronic conductors with σ values lying in the order of 10–6 Ω–1 m–1 around 300 K and increases with increase of temperature.